P3.147 Prevalence of HIV/STIs and Risk Behavior in Men Who Have a Sex with Men, Belize, 2012. (13th July 2013) - Morales-Miranda, S; Alvarez, B; Manzanero, M
Abstract : Background: In Central America, the HIV epidemic is primarily concentrated in a few populations; including men who have a sex with men (MSM). The lack of reliable HIV prevalence estimates among MSM has impacted HIV programme planning targeting this population. In 2012, we conducted the first biological and behavioural survey among MSM in Belize. Methods: From January - July 2012, we used respondent-driven sampling to recruit MSM in four districts of Belize. Data was collected using a behavioural survey questionnaire administered through audio computer-assisted self-interview (ACASI). All participants were tested for HIV, syphilis and herpes simplex virus type 2 (HSV-2). Additional genital specimens collected were tested for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV), and Mycoplasma genitalium (MG) using polymerase chain reaction (PCR). Proportions, medians and interquartile ranges (IQR) were calculated using STATA 9.0. Results: A total of 130 MSM were enrolled. Of these, 64.7% self-identified as gay/homosexual, 32.3% as bisexual, and 2.9% as transvestite/transgender. Median age was 26 years old (IQR 22–31.5). Overall, 37.6% reported sex with a woman in the last 12 months. Consistent condom use with occasional, client, and commercial male partners in last 12 months was reported by 64.4%, 75.0% and 50.0%, respectively. HIV prevalence among MSM was 13.8%, HSV-2 was 27.9%, followed by genital CT 6.9%, anal CT 4.3%, NG anal 2.9%, MG genital 2.8%, and syphilis and active syphilis < 1%. Conclusions: Our findings show high prevalence of HIV in MSM in Belize. Despite the low STI prevalence observed, we found high rates of risky sexual behaviour. Development of strategies for HIV and STI prevention in sexual health services, focusing on improved condom access and promotion are urgently needed.